Babylonia, Fantasy, Complex and Reality: On Eli Amir's Farewell, Baghdad - Drori, Itamar (MiKAN, 2017)
This article offers a new reading of the novel Farewell, Baghdad (Mafriah Ha-Yonim,1992) by Eli Amir. This reading undermines the perception of the novel as a political pro-Zionist one. Through tracing the language of the characters in the novel as well as the symbolism and imagery, another layer emerges alongside the necessity to leave the Diaspora and immigrate to Israel. In this sphere, the Jews of Baghdad(Babylonia) perceive their homeland as a primal mythical space, and leaving that space is tantamount to disaster. This attitude is for the most part, subconscious ,and parallels Freud's primal fantasy (Urphantasie). The second part of the article demonstrates that this fantasy is accompanied by a Freudian complex known as the Madonna-whore complex toward the Babylonian homeland, a complex central to the desertion of the homeland. This complex is the reason the desertion is incomplete and riddled with hesitation, reservations, and regret.